Weight training and risk of subsite-specific colorectal cancer - Boyle, T.; Heyworth, J.; Bull, F.; Fritschi, Lin (Oxford University Press, 2011)
There is convincing evidence that physical activity reduces colon cancer risk. However it is unclear whether different types of activity, such as aerobic and anaerobic activity (e.g. weight training), have a different effect on risk. We conducted a case-control study to investigate whether weight training was associated with the risk of subsite-specific colorectal cancer. A total of 918 cases and 1021 controls participated in a case-control study of colorectal cancer in Western Australia in 2005-07. Cases were histologically confirmed incident cases of colorectal cancer and age and sex matched controls were randomly selected from the electoral roll. Data were collected on demographic and lifestyle-related colorectal cancer risk factors, including recreational physical activity performed over the adult lifetime. The estimated effect of weight training on the risk of cancers of the proximal colon, distal colon and rectum was analyzed using multinomial logistic regression. After adjusting for potential confounders, including energy expenditure in recreational physical activities other than weight training, participants who did any weight training had a non-significant 37% lower risk of distal colon cancer than those who did no weight training (Adjusted Odds Ratio ¼ 0.63, 95% Confidence Interval 0.32, 1.24). Weight training was not associated with rectal cancer or proximal colon cancer. These results suggest that weight training may be inversely associated with distal colon cancer risk, independently of other recreational physical activity, although the low prevalence of the exposure resulted in insufficient power to detect a significant difference. Further studies are needed to confirm this novel finding.